W służbie Chrystusowi. Błogosławieni prezbiterzy i osoby zakonne Archidiecezji Poznańskiej - Kijas, Zdzisław (Poznańskie Studia Teologiczne, 2018)
The subject-matter of the article is the issue of sanctity which the author considers in the context of the lives of seven men and one woman. All of them belong to the Poznań Church. Their heroic lives provide an opportunity to scrutinize contemporary culture, which is characterized by a process of disenchantment of the world, i.e. humanization of what formerly used to be divine, what belonged to God or led to Him. Today we witness a tendency to sanctify things human, things which are the work of man and enhance human pleasure, enjoyment of life and cheerful disposition... At the same time things divine and those that lead to God are dismissed or even forgotten. Modern man has become increasingly autonomous. He no longer needs God seeing Him as unwanted or even redundant. Prayer, which animates saints, is now considered mere waste of time while obedience to God’s commandments is deemed ridiculous. This process also impacts our attitude to the saints. In Christian theology they are the teachers of the faith, witnesses of God and His truth. They are the good Samaritans that lift up those who fell, reminding them of their dignity received from God and encouraging them to go ahead to meet God. But many of our contemporaries, believ- ers included, no longer perceive saints in this way. They do not expect from the saints lessons on life, but miracles in order to have a rich, healthy and happy life themselves. They look for miracle workers not witnesses and teachers of God’s truth, the prophets of a different world. As God’s wit- nesses the blessed and saints can “hold back” the process of disenchantment of the world and give the world a new eschatological dimension, the lost sacrum without which life on earth can change into a drama.